THE EFFECT OF INTELLECTUAL CAPITAL AND COMPANY SIZE ON STICKY COST - Wira Ramashar; Della Hilia Anriva; Zul Azmi; Intan Diane Binangkit (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2019)
Sticky cost behavior becomes very important to know because sticky cost behavior can give a bad influence on the company in terms of obtaining the desired level of profit. By obtaining information about sticky cost behavior, it is expected that company management can be more careful in planning, controlling and making policies or decisions. This study aims to analyze and explain: (1) The effect of Intellectual capital on sticky cost and (2) the effect of company size on sticky cost. The population of this research is the manufacture companies listed on the Indonesia Stock Exchange (BEI) in 2014-2017. The total samples of this research are 46 companies. Technical analysis of data in this study is using WarpPLS 5.0. The results of data analysis prove that: (1) Intellectual capital has no significant effect on sticky cost, (2) company size has a significant effect on sticky cost.